Micro and macro evidence of the relationship between income mobility and taxation - Ådne Cappelen; Aurora G. Hattrem; Thor Olav Thoresen (Statistics Norway, Research Department, 2024)
How taxation influences income mobility is largely a neglected topic. In this study we discuss the relationship between taxation and income mobility by analyzing both macro and micro data. Administrative register data based on income tax returns are used to produce individual and aggregate measures of income mobility from 1994 to 2021. Income mobility is explained in terms of marginal tax rates on both wage income and capital income. Estimation results are obtained from an autoregressive distributed lag model and a fixed effects linear probability model for the macro and micro data approaches, respectively. The macro and micro evidence point in the same direction - we find that income mobility is negatively influenced by higher marginal tax rates on both earnings and capital income, with the largest effect found for tax on capital income.
Keywords: D31; H24; H30; 330; Income mobility; tax effects; administrative register data